Análise multitemporal dos ajustes morfológicos no baixo rio São Francisco (Nordeste, Brasil): impactos da barragem de Xingó na dinâmica fluvial - Gomes, Pedro Victor Oliveira (2021)
After successive impoudments of 6 big dams stations troughout the last hundred years, particularly after the facility of Xingó was build , the lower course of São Francisco River (LSFR) suffered a reduction in the average water discharge and is no longer capable to transport most of sandy bed load sediments towards its mouth. Nevertlheless, a discussion assessing the role of dams and climate changes on the São Francisco River morphological ajdustments is scarce. In order to fullfill that gap and evaluate the role of Xingó´s reservoir on morphological adjustments we focused on the characterization and quantification of the morphological adjustments in the LSFR. To do so, a time series of satellite images were chosen, and water, sediment discharges data were used along seventeen reaches. To assess the influence of climate change along the drainage basin we carried out a linear regression aproach using a pre and postdam time series comparison along. Our satellite images demonstrate a predominance of internal adjustments to the channel in relation to external ones, with low values of lateral migration rate and little variation in channel sinuosity. After the construction of the Xingó dam, the percentage of sand bars remained constant in the groups closest to the dam (G1 and G2), while G3 presented an increase in bed forms. However, with the decrease in water discharges due to the decrease in rainfall in the river basin, sediments started to be deposited closer and closer to the dam. This process is also responsible for increasing the channel interlace rate in the LSFR. It is during this period of prolonged drought (2013-present) that the largest decreases in channel width occurred in all LSFR reaches. This dry period was responsible for the 40.4% decrease in discharges in the post-Xingó period, representing the main control over the decrease in water discharge and the morphological adjustments resulting from this decrease. Thus, the reduction in effluent discharges from Xingó, and from other dams upstream, is largely a consequence of lower rainfall in the drainage basin.